One-into-Five Labor-Grouping for Watershed Management in Northwest Ethiopia: Farmers’ Acceptable Participation and Influencing - Mosseye, Tibebu; Belay, Mehretie (Ethiopian Journal of Social Sciences, 2018)
Participation in community labour-sharing links promotes the interest of households to work in groups and reinforces their public affairs with client households. However, numerous factors appear to influence household participation in community labour-sharing groups in many parts of Ethiopia and elsewhere in the world. This paper presents the results of a study made on households’ acceptance and participation in the One-into-five developmental groups organized by government agencies for watershed conservation purposes in Machakel Woreda, in the northwestern highlands of Ethiopia. It specifically aims to: i) identify the types of labour-sharing teams operating in the study woreda; ii) examine households’ alleged participation in the One-into-five labour associations; iii) assess the areas and rates of household participation in the One-into-five developmental groups during the watershed management campaigns; iv) describe the benefits of soil and water conservation (SWC) structures installed by the new politically enforced One-into-five labour-groups; and v) appraise the factors influencing acceptable household participation in the mentioned labour- teams during the watershed management campaigns. To address the objectives, data were gathered through field observation, focus group discussion, key informant interview, and a questionnaire survey of 135 households from January to March 2015. Descriptive statistics, T-test, Chi-square test and binary logistic regression model were used to analyze the data. Debo, wonfel and One-into-five farmer labour-sharing associations that are operating in the study areas have been examined. The study revealed that over 33% of the households participate in wonfel and in the One-into-five labour-sharing teams. Over 82% of the households participate in the One-into-five farmer groupings against their will. Most households in the study areas consider watershed based SWC community works as mandatory and forced development tasks. Conversely, restoration of degraded lands, improvements in soil fertility levels after rills and gullies stabilized, and increment of crop yields were found to be the major benefits of SWC structures installed by the One-into-five labour associations. Participation in the off-farm business, the slope of the land under conservation, farmland size, and participation in the indigenous labour associations emerge to significantly and positively influence the acceptable participation of the households in the One-into-five labour-groups. Conversely, livestock asset and access to training appear to significantly decrease the households’ acceptable participation in the mentioned labour team during the watershed SWC works. It is suggested that indigenous labour-sharing teams be promoted and strengthened to ease households’ workloads and consolidate the established work habits instead of focusing on a top-down imposed alien and new association that cause doubts in the society.